IDENTITÉS CIRCONSTANCIELLES ET MÉTAMORPHOSES DU MOI - N’CHO, Rachel (European Scientific Journal, ESJ, 2012)
﻿The need of use and display multiple identities is the "social marker" which allows to identify in human the desire for more freedom, faced with the constraints of a changing society. Therefore, the theater which promotes is fictional and dramatic expression happens to be the privileged space of the “making face to face” of different identities that form, transform and correct in the circumstances of the show. The process of communicative interactions, involved in these exchanges highlights, a set of identities dialogue through strategical negociation between individual identity and collective identity. Symbol of human socialization, the fluctuating identities and therefore circumstantial identities, as regulators of the self image, play an important and even essential role in the formation of actor and the public individual personality, in social cohesion, and the construction of a new society.